Advances in analytical techniques for assessing volatile organic compounds in pulse crops: a comprehensive review - Makhlouf, Leila; El-Fakhouri, Karim; Kemal, Seid Ahmed; Aasfar, Abderrahim; Meftah Kadmiri, Issam; El Bouhssini, Mustapha (Frontiers Media, 2024)
Pulse crops, including beans, peas, chickpeas, and lentils, are vital sources of protein, fiber, and essential nutrients worldwide. They serve not only as staple foods but also as key components of sustainable agricultural practices, contributing to soil fertility through nitrogen fixation and enhancing overall productivity. However, pulse crops face numerous abiotic and biotic stresses mainly insect pest attack and pathogen invasion, which pose significant threats to pulse crops, impacting both production and food security. To overcome these challenges, plants have evolved diverse defense mechanisms, including the emission of specific volatile organic compounds (VOCs). These volatiles play crucial roles in plant communication, protection, and real-time health status indication. Monitoring VOCs offers a promising approach for early detection of pest infestations or pathogen infections, enabling the grower to take early action and decide on the proper control measure to minimize losses. The identification of plant-emitted VOCs requires robust and sensitive analytical techniques such as gas chromatography and mass spectrometry, which are the mainly used techniques for in pulse crops studies. However, traditional methods have limitations, prompting the need for advanced, portable, and real-time detection alternatives, such as gas-sensing technologies. This paper provides a comprehensive review of VOC measuring methods, including extraction, separation, and analytical techniques, focusing on their application in pulse crops. Recent advancements in gas-sensing technologies are also discussed, highlighting their potential in enhancing crop protection and agricultural sustainability.